CEDAW and the Istanbul Convention : A comparative view on transposition and implementation in domestic law and practice.: A comparative view on transposition and implementation in domestic law and practice. (2021) - Orme, Stephen; Northern Ireland., Assembly., Research and Information Service,
No abstract available